Combination of Femoral and Parasacral Sciatic Nerve Block as Multimodal Pain Management in Post Hemiarthroplasty Surgery Patient - Faundra Arieza Firdaus; Ristiawan Muji Laksono (Faculty of Medicine, Brawijaya University, 2023)
Background: The prevalence of femoral neck fractures is high in geriatric patients with a high mortality rate. Many geriatric patients have comorbidities and find it difficult to tolerate general or neuraxial anesthesia during hip hemiarthroplasty. A more safe technique in lower extremities using peripheral nerve blocks is preferred. The combination of sciatic nerve blocks and psoas compartments can supply adequate anesthesia for hip surgery thus reducing mortality. Femoral nerve blocks decrease the incidence of complications than psoas compartment blocks.Case: A 88-year-old female patient, 70 kg, with distal femoral subtrochanteric fracture accompanied by dislocation, hypertension emergency, hyperplasia heart disease (HHD), and heart failure stage B Fc II were undergoing hemiarthroplasty with regional anesthesia sciatic nerve block and femoral block. After surgery, a block was performed using regional anesthesia sub-arachnoid block bupivacaine 0,5% 7mg + fentanyl 25 µg + Morphin 0,1 µg, post-operative pain with ultrasound, the patient received 0.375% naropin and 50 mg trilac total volume 20 cm3. Then femoral block was done with 0.375% and 50 mg trilac total volume 20 cm3. Patients were observed for pain scale during hospitalization, time of mobilization, and length of stay. Post-operative hemodynamic was stable, the pain scale using VAS assessment was 0-1 during hospitalization without additional opioid analgesia, active mobilization began on the 2nd day, and the length of stay was 3 days.Conclusion: The combination of a femoral and sciatic nerve block to the proximal part of the skin incision can supply adequate pain compliance for hip hemiarthroplasty.